Teaching Foreign Students-Non-philologists Russian Language: Approaches, Aspects, Experience. - Гейченко, Е. И. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The problems of training Russian language communication to foreign students of non-linguistic specialties have been considered in the article. The compliance of approaches to training communicative requirements to this contingent of students has been analyzed. The problems of interpretation of the main terms existing in modern language teaching methods have been outlined. The main tasks and peculiarities of teaching foreign language learners written and oral speech, the possibilities of using the experience in mastering the native language have been described